2012
DOI: 10.4103/1319-3767.91739
|View full text |Cite
|
Sign up to set email alerts
|

Measuring of gastric emptying in Egyptian pediatric patients with portal hypertension by using real-time ultrasound

Abstract: Background/Aim:Among the various methods for evaluating gastric emptying, the real-time ultrasound is safe, does not require intubation, or rely on either radiologic or radionuclide technique. The aim of our work was to measure the gastric emptying in pediatric patients with portal hypertension by using the real-time ultrasound.Patients and Methods:Forty patients with portal hypertension with mean age 7 ± 2.8 years and 20 healthy children as a control group underwent gastric emptying study by using real-time u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Although parameters of malnutrition may correlate with delayed gastric emptying, a clear correlation has not been reported in malnourished patients with Crohn's disease . One study found statistically significant delayed gastric emptying in patients with portal hypertension compared to healthy controls, postulating that delayed gastric emptying can lead to or aggravate portal hypertensive gastropathy . Patients with diabetes mellitus type I, Turner's syndrome, pancreatic insufficiency, and cystic fibrosis have a higher prevalence of gastroparesis than the standard population .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although parameters of malnutrition may correlate with delayed gastric emptying, a clear correlation has not been reported in malnourished patients with Crohn's disease . One study found statistically significant delayed gastric emptying in patients with portal hypertension compared to healthy controls, postulating that delayed gastric emptying can lead to or aggravate portal hypertensive gastropathy . Patients with diabetes mellitus type I, Turner's syndrome, pancreatic insufficiency, and cystic fibrosis have a higher prevalence of gastroparesis than the standard population .…”
Section: Resultsmentioning
confidence: 99%
“…Data on other gastric motor function tests used in adults are still limited in children. Several studies report utility of ultrasound as a non‐invasive measure of proximal and distal compartment sizes and antral contractility in response to a meal . In one study, distention of antrum rather than gastric emptying time as measured by ultrasound correlated with worse dyspeptic scores in a subgroup with delayed gastric emptying .…”
Section: Resultsmentioning
confidence: 99%
“…All parts of the gastrointestinal tract can be affected. Numerous studies have reported delayed gastric emptying in patients with cirrhosis and portal hypertension compared to healthy controls [ 101 , 102 , 103 ]. Intestinal motility can be affected, with altered timing, frequency and amplitude of contractions described [ 104 , 105 , 106 ], with cirrhotic patients with portal hypertension being more frequently affected than those without portal hypertension [ 105 ].…”
Section: Complications Of Portal Hypertension and Their Role In Malnu...mentioning
confidence: 99%